How science tracks understanding - Malfatti, Federica Isabella (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2023)
This review article discusses the book Understanding How Science Explains the World by Kevin McCain, published by Cambridge University Press (2022). With an impressive combination of clarity and depth, McCain provides the reader with a firm grasp of how science works, of what science aims to achieve, and of what makes science a successful epistemic enterprise. The review article reconstructs the book’s overall dialectic and identifies one potential point of tension which concerns the role of truth or accuracy in scientific knowledge.
Keywords: Truth; scientific realism; understanding; Explanation; scientific knowledge